FAKTOR-FAKTOR YANG MEMPENGARUHI PERAN MEDIA KOMUNIKASI DALAM SELEKSI KONSUMSI PRODUK PERTANIAN - Raya, Alia Bihrajihant; Harsoyo, Harsoyo; Witjaksono, Roso; Sarmiasih, Yuli (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2011)
Abstract This research has aimed to know the factors that influenced on the role of communication media such as interpersonal media, group media, and mass media on selecting agricultural product. This research was conducted at Depok Sub-district residence and Gamping sub-district residence in Sleman Regency. The Depok sub-district was taken to represent urban area and Gamping sub-district to represent rural area. Simple random sampling was used to choose residence sample. Every sub district was taken 30 respondents so the total respondents were 60 person. In this research used descriptive analytical and explanative method. Chi-Square test was used to identify the factors that influenced on the role communication media such as interpersonal media, group media, and mass media on selecting agricultural product. The result showed that factors such as age, educational level, occupation, media's ownership, and media's credibility had influenced on the role of interpersonal media. The factors such as occupation and media's ownership had influenced on the role of group media. The factors such as educational level, occupation, family's income, media's ownership and media's credibility had influenced on the role of mass media